Konstytucyjne zasady partycypacji zbiorowości w sprawach publicznych - Wołupiak, Waldemar J. (Constitutional principles of community participation in public affairs, 2005)
The contents of this paper are the analysis of legal aspects of community participation in Poland from the point of view of constitutional regulations. From this analysis appears that on the basis of previously binding constitutional norms in compliance with Marxist ideology, the community decided about public behavior of an individual, whereas nowadays the regulations of Polish Constitution ensure for individuals participation in various forms of public affairs. Furthermore are analysed the problems of participation in public affairs of abstract subjects (nation, citizens, inhabitants), organized subjects (parties, associations, trade unions, self-governments etc.), non-govemmental structures and special interest groups.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1090, s. 9-25